The Role of NGO In Community Empowerment (Case Study LPPSLH Penderes Empowerment in Pasinggangan Village, Banyumas Regency) - Dita Aprilia; Ageng Widodo (Prosperity: Journal of Society and Empowerment, 2021)
Behind the life that we see in the capital city, it turns out that we still know the phenomenon of people's lives in rural areas who still depend on the natural resources around them. One of them is the phenomenon of coconut sugar farmers, who are often called penderes, who still cannot process coconut sap correctly and adequately to increase the selling value of the sugar. It is due to the low level of education and the lack of public knowledge in processing coconut sugar. LPPSLH is a non-government institution engaged in community empowerment, both urban and rural. With the phenomenon experienced by the farmers, LPPSLH as a facilitator, invites the farmers to take part in the organic certification program for ant sugar. Later, it can increase the farmers' income, increase the selling value of sugar, and market their products to the export market. The training and assistance aim to change farmers' behavior and old habits into more productive and profitable habits (efforts) to build farmers' independence. The method used in this research is descriptive-qualitative, and the sampling was collected purposively. The data collection technique used interviews, observation, and documentation. The results showed that LPPSLH played the role of education, facilitation, and advocacy to penderes farmers in empowerment programs, especially in rural areas.